Investigation of corrosion behaviour of Al 7075 / B4C / Al2O3 hybrid metal matrix composite. (2022) - Sambathkumar, M.; Gukendran, R.; Vijayanand, M.
Abstract: This work is carried out in order to develop a metal matrix composite material which has better strength, light in weight and has better corrosion resistance. Different engineering materials are used in different application like food industries, oil refinery industries, Automobiles and aerospace industries. Reduction of corrosion rate in engineering materials will increase the life span of the materials. The corrosion and mechanical behaviour of Al 7075 alloy composites with reinforcement of aluminium oxide (Al2 O3 ) and boron carbide (B4 C) particle is studied in this work. Having the properties like lightweight and high strength, the application of Al 7075 alloy can be used in the structures of aircrafts, gears and shafts. This alloy can be manufactured by stir casting method which is of very economical than the other methods. By varying the volume fraction of aluminium oxide and boron carbide in the percentage ratios 5%, 10% and 15% the characteristics are studied. The reinforcement particles are distributed in the matrix and the microhardness test is conducted using Vickers hardness tester. The corrosion rate is calculated by Potentiodynamic polarization method with 3.5% wt. of Nacl solution. The corrosion rate of Al 7075 + 15 vol% hybrid composites shows 0.336 mm/year. It is found that, stir casting method is very much suitable to achieve the even distribution of reinforcements in the composite mixture, which led to better micro hardness of the material with better corrosion resistance compare to the base as cast alloy.